Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1111/j.1537-2995.2011.03480.x
|View full text |Cite
|
Sign up to set email alerts
|

Toward a prophylaxis against fetal and neonatal alloimmune thrombocytopenia: induction of antibody‐mediated immune suppression and prevention of severe clinical complications in a murine model

Abstract: This work conceptually proves that prophylactic administration of PLT antibodies induces AMIS and prevents poor pregnancy outcome in FNAIT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 40 publications
2
45
0
1
Order By: Relevance
“…Currently, no specific treatment is available to prevent FNAIT; nor is there any specific therapy. However, a strategy to prevent alloimmune thrombocytopenia by Ab prophylaxis has been proved successful in mice (10), and clinical trials (http://www.profnait.eu) are under way to test the potential of hyperimmune anti-HPA-1a IgG in preventing HPA-1a immunization in connection with pregnancy (9). In principle, HPA-1a-specific mAbs may be as efficient as polyclonal antisera in preventing alloimmunization and could hold important advantages, not the least in terms of tailorability, for enhanced function and as a limitless source of such Abs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, no specific treatment is available to prevent FNAIT; nor is there any specific therapy. However, a strategy to prevent alloimmune thrombocytopenia by Ab prophylaxis has been proved successful in mice (10), and clinical trials (http://www.profnait.eu) are under way to test the potential of hyperimmune anti-HPA-1a IgG in preventing HPA-1a immunization in connection with pregnancy (9). In principle, HPA-1a-specific mAbs may be as efficient as polyclonal antisera in preventing alloimmunization and could hold important advantages, not the least in terms of tailorability, for enhanced function and as a limitless source of such Abs.…”
Section: Discussionmentioning
confidence: 99%
“…A prophylactic strategy to prevent FNAIT occurrence using anti-HPA-1a Abs derived from pooled donor plasma has been proposed (9). Such a strategy has been proved to prevent thrombocytopenia in newborn pups in a murine model of FNAIT (10). An attractive source of anti-HPA-1a Abs for eventual FNAIT prophylaxis or therapy would be human mAbs.…”
mentioning
confidence: 99%
“…Although the mechanisms behind this process remain largely unknown, a mouse model of fetomaternal platelet alloimmunization demonstrated that administration of platelet anti-b3 antibodies prevented alloimmunization. 42 Here, we have shown that B2G1 very quickly clears HPA-1a-positive platelets from the circulation and would therefore constitute an ideal candidate to progress on to clinical studies for prophylaxis after delivery in HPA-1a-negative women. If this proved to be effective, one could consider follow-on studies to assess effectiveness of this prophylactic approach during pregnancy, in particular including primigravidae where alloimmunization can lead to significant fetal thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical management of FNAIT is still a challenge (1,3,4,61), but IVIG has been demonstrated to be a useful therapy for this disease. We previously demonstrated that IVIG downregulated both maternal and neonatal circulating levels of anti-platelet antibodies (40), although IVIG did not show antiidiotype activity and did not significantly inhibit the binding of anti-β3 antibodies to platelets (40).…”
Section: Detection Of Anti-β3 or Anti-gpibα Antibodies Via Flow Cytommentioning
confidence: 99%